Estimating trap distribution and intertrap charge transfer in SrZnO2 nanoparticles. (January 2020) - Manju,; Jain, Megha; Sen, D.; Vij, Ankush; Thakur, Anup
Abstract: Oxide nanoparticles often exhibit interesting properties due to the presence of various defect states in the band gap. Thus, understanding the defect states is essential for determining the potential utility of these materials in various applications. In the present study, we analyzed the trapping states in SrZnO2 nanoparticles based on the thermoluminescence (TL) at various gamma radiation doses (50 Gy, 100 Gy, 500 Gy, and 1 kGy). The crystal structure and lattice parameters were derived by Rietveld refinement of the X-ray diffraction patterns. The TL glow curves produced by the SrZnO2 nanoparticles indicated the presence of trap distributions in the temperature ranges from 50-150 °C and 250–400 °C. The average activation energies for shallow and deep traps were determined as 0.9 eV and 1.2 eV, respectively, which were calculated by computerized glow curve deconvolution of the glow curves using a general order kinetics approximation. The TL curve maximum occurred at 500 Gy and further increase in the irradiation dose resulted in retrapping of the charge carriers from shallow traps to deep traps. This phenomenon can be explained using a band model.